New method for point-of-care osteoporosis screening and diagnostics. Issue 3 (March 2016) - Karjalainen, J.; Riekkinen, O.; Töyräs, J.; Jurvelin, J.; Kröger, H.
Abstract Summary Due to the lack of diagnostics in primary health care, over 75 % of osteoporotic patients are not diagnosed. A new ultrasound method for primary health care is proposed. Results suggest applicability of ultrasound method for osteoporosis diagnostics at primary health care. Introduction We lack effective screening and diagnostics of osteoporosis at primary health care. In this study, a new ultrasound (US) method is proposed for osteoporosis diagnostics. Methods A total of 572 Caucasian women (age 20 to 91 years) were examined using pulse-echo US measurements in the tibia and radius. This method provides an estimate of bone mineral density (BMD), i.e. density index (DI). Areal BMD measurements at the femoral neck (BMDneck ) and total hip (BMDtotal ) were determined by using axial dual-energy X-ray absorptiometry (DXA) for women older than 50 years of age (n  = 445, age = 68.8 ± 8.5 years). The osteoporosis thresholds for the DI were determined according to the International Society for Clinical Densitometry (ISCD). Finally, the FRAX questionnaire was completed by 425 participants. Results Osteoporosis was diagnosed in individuals with a T-score −2.5 or less in the total hip or femoral neck (n  = 75). By using the ISCD approach for the DI, only 28.7 % of the subjects were found to require an additional DXA measurement. Our results suggest that combination of US measurement and FRAX in osteoporosis management pathways would decrease the number of DXA measurements to 16 % and the same treatment decisions would be reached at 85.4 % sensitivity and 78.5 % specificity levels. Conclusions The present results demonstrate a significant correlation between the ultrasound and DXA measurements at the proximal femur. The thresholds presented here with the application to current osteoporosis management pathways show promise for the technique to significantly decrease the amount of DXA referrals and increase diagnostic coverage; however, these results need to be confirmed in future studies.